FOXO1 and FYN Expression Trends in Breast Cancer Stem Cells: An Integrative Study of Single Nucleotide Polymorphism (SNP) Array and Quantitative PCR (qPCR) Analysis - Ay Ly Margaret; Septelia Inawati Wanandi; Fadilah Fadilah; Rafika Indah Paramita (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Currently, identification of breast cancer stem cells (BCSCs) commonly relies on CD24-/CD44+ expression profiles. However, few studies have integrated genomic mutation data with experimental gene expression validation in CSC and non-CSC populations. Genotyping results of CD24-/CD44+ MDAMB-231 cells revealed 36 mutations in BCSCs compared to non-BCSCs, with upregulated FOXO1 and FYN that might represent promising candidate biomarkers for this subpopulation. Therefore, in this study, single nucleotide polymorphism (SNP) and quantitative polymerase chain reaction (qPCR) analysis were performed to assess the association between mutations and expression trends of FOXO1 and FYN in MDAMB-231 cell, as breast cancer cell model with stem-like traits and well-characterized profile.METHODS: Genomic DNA was isolated from BCSC and non-BCSC DNA from the MDAMB-231 cell line. Mutation analysis was conducted using PLINK, while gene expressions of FOXO1 and FYN were quantified by one-step SYBR Green-based qPCR, using 18s rRNA as a reference. Data was then analyzed with the Livak (2−∆∆Ct) method.RESULTS: Among 36 mutations found in BCSCs of the MDAMB-231 cell line, PTEN (rs786204914) and CHEK2 (rs587782401) were identified as pathogenic. While FOXO1 (2.989±2.817 vs. 1.072±0.388) and FYN (1.405±0.072 vs. 0.855±0.140) mRNA levels were found to be higher in CSCs compared to non-CSCs, though these differences was not statistically significant.CONCLUSION: Pathogenic mutations in CHEK2 and PTEN were detected within BCSC population, implying a potential influence on the expression of FOXO1 and FYN, though not statistically significant. These findings suggest a possible, but as yet unverified, association between gene mutations and expression patterns, emphasizing the importance of further functional studies to validate FOXO1 and FYN as biomarkers for BCSCs.KEYWORDS: breast cancer stem cells, FOXO1, FYN, PTEN, CHEK2, mutation, biomarker